Exploring the Relationship of Competency, Management Best Practices, and Employee Performance in a Palm Oil Mill Company - Hermailinda Evianisa; Anggraini Sukmawati; Alim Setiawan Slamet (Bina Nusantara University, 2021)
In managing human resources, management is required to find appropriate competency development. Theemployees need to know what competency indicators they have and should have. It needs to be done to encouragethe best practices provided by management to improve employee performance. The research aimed to identify thecompetency of human resources and management best practices related to advancing employee performance in apalm oil mill company. The research applied a quantitative approach. The studied company was Talopino palm oilmill unit in Seluma Regency, Bengkulu, owned by PT Perkebunan Nusantara VII Lampung (PTPN VII Lampung).The research was conducted from July to November 2019. The used data were primary and secondary data.Primary data were obtained by interviews and questionnaires with 76 employees in the company. The indicatorswere adapted from several previous researchers. The research analyzed the data using the Likert scale and PartialLeast Square Structural Equation Modeling (PLS-SEM). The result shows three implications. First, competencyaffects employee performance in the palm oil mill company. Second, competency has an insignificant result onmanagement best practices. Third, management best practices affect employee performance. The research canprovide information to companies in enhancing the employees’ competency with strategic steps in the era ofglobalization.